The Effect of Giving Temulawak Honey Cookies (Curcuma zanthorrhiza) on Toddler Weight Gain - Yustin Ari Prihandini; Dita Ayulia Dwi Sandi; Nurul Mardiati; Rahmi Hidayati; Vebruati Vebruati (Jurnal Berkala Kesehatan, 2022)
Nutritional problems in South Kalimantan need more attention. This is because toddlers (aged 0-59 months) who experience nutritional problems in the Weight/Age (W/U) indicator, namely the poor nutrition category, are at a prevalence of 5.5% above the national figure of 3.9% Data from the Banjarbaru Guntung Payung Health Center based on BB/U there are toddlers with poor nutritional status as much as 36% and poor nutritional status as much as 11%. One of the efforts to prevent undernourished children under five is by Quasy experimental research design with One Group Pre test and Post test designs. The research sample was 30 toddlers aged 24-59 months who were undernourished according to age as a result of weighing at the Guntung Payung Health Center in May-June 2021. The general purpose of this study was to modify supplementary feeding (PMT) to toddlers by giving honey and ginger supplements in cookies to improve the nutritional status of toddlers or toddlers to normal nutritional status. The research instrument used was a questionnaire and direct weighing of children under five. Descriptive and statistical data analysis used paired t-test. The results of the paired t test showed that there was an effect of giving ginger honey cookies (Curcuma zanthorrhiza) (p=0.000) on the weight gain of toddlers in Guntung Payung Village, Banjarbaru.